Casein phosphopeptide-amorphous calcium phosphate nanocomplex (CPP-ACP) in dentistry: state of the art - Madrid-Troconis, Cristhian Camilo; Perez-Puello, Sthefanie del Carmen (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Saliva and external agents containing different concentrations of sodium fluoride (NaF) promote the dental remineralization process. However, these resources may not be sufficient to counteract the multiple factors involved in the process of dental caries, especially in high-risk patients. There are alternatives that have been extensively researched, such as casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) which provides essential ions, like phosphate and calcium, acting as an adjuvant in the remineralization process. Manufacturers of CPP-ACP-based products also suggest that it can produce desensitizing effects. This nanocomplex has been used experimentally with some dental cements and adhesive systems, but it is important to clarify the effects of this procedure, and the remineralizing/desensitizing advantages it offers. The objective of this topic review was to present the state of the art on CPP-ACP nanocomplex. In terms of dental caries prevention, this remineralizing option is not better than NaF. CPP-ACP provides a dental desensitizing action, but it is temporary and less effective than other alternatives such as potassium nitrate or NaF. The experimental incorporation of CPP-ACP into dental cements should be controlled for not to compromise the physico-chemical properties of the material. The use of dental products based on this nanocomplex as dental surface pretreatment may decrease the bond strength of adhesive materials, but this effect is material dependent.